Diseño de una máquina extrusora-inyectora de plásticos de baja densidad. - Acuña Ruiz, Alex Patricio (2020)
The multifunctional team approach is the key to value creation, especially considering that strategic supply allows for the feasibility of integrating functions into small teams and, in turn, reflects a process of continuous improvement, where multifunctional teams play a fundamental role. in the plastic manufacturing markets. The adaptation of systems to small monofunctional machines for experimental use in the academy allows engineering students to perceive new computational tools that facilitate mechanical engineering design, achieving that a single machine that previously fulfilled a single function and delivered a single product can now generate functions and integrate their systems to generate more diverse production, managing to be competitive with quality products. This project is focused on the design of a system for the low-density plastic injection molding process, taking as reference parameters and characteristics of an existing plastic extrusion machine in the Electromechanical Engineering Career Laboratory, the same ones that served as the basis for the analysis and adaptation of the new system, having the extrusion screw as a strategic tool for the combination of the two plastic molding processes, since this also gives rise to the injection system, this being the one that gave the opportunity to double Depending on the machine, the design study focuses on processing low-density plastic ranging from 0.910 – 0.940 gr/cm3. In this case, the MR50A is used with a melting temperature of 130°C. The machine processes an injection mass of 11.34 gr that generates a small-scale production, the mold for this system is built and mounted to the machine by means of 4 fastening bolts and they comply with the support for the injection pressure of 22.1 Mpa, delivering injected parts that reach a satisfactory and consistent quality according to engineering criteria. The design and adaptation of the system was carried out with the Solidworks computer-aided software and the structural analysis of the design using the ANSYS Software, tools used in mechanical designs.